Recontando histórias: a leitura e a visão de mundo do pré-escolar. - Donato, Daniela (2005)
In this work we analyze the perception of the world traces conveyed by pre-school children when they retell stories. From the cultural historical perspective and from some aspects of textual linguistics, 58 retellings, produced in the story retellings classes of two Municipal Pre-Schools of the city of Matão in São Paulo, were analyzed. Four common types of occurrences were detected: oral marks, ways of telling, insertion of the quotidian, insertion of new elements, which were divided up into 22 subcategories to be analyzed. These data, which were considered as singular ones, show us that the world perception is present in the whole process of story telling, mainly when the children insert elements of his/her daily routine in the narrative, and the purpose of this is always the production of sense. We believe that the knowledge of these traces may lead the teacher to develop a better understanding of his/her task on the children education as good readers, and good writers. In short, on the formation of a child who tomorrow may know how to invent man.